The Dynamism of East Asian Economic Integration - Mustafa, Rujhan (Universiti Malaysia Sarawak (UNIMAS), 2005)
The East Asian economic integration started in 1990 due to increase regionalism in Europe and North America and the difficulties of concluding the Uruguay Round of trade negotiation